Production and reproduction performance of bovines in Bulandshahr district of Uttar Pradesh - SHAH, DEEPAK; SHARMA, K N S (The Indian Journal of Animal Sciences, 2013)
The comparative performance of different breeds of milch animals in Bulandshahr district (Uttar Pradesh) was studied utilizing data collected in the area during 1989-90. The data revealed that age at first calving was lower for crossbred cows (35 months) than for Murrah buffaloes (39 months), local huffaloes (42 months) and local cows (45 months). The lactation length was longer for Murrah buffaloes (358 days) than crossbred cows (355 days), local buffaloes (338 days) and local cows (327 days). The dry period observed was the least forcrossbred cows (85 days) followed by Murrah buffaloes (97 days), local buffaloes (106 days) and local cows (132 days). The average intercalving period was the least for crossbred cows. Onan average, the percentage of animals in milk was 75.lt was further observed that crossbred cows registered the highest per day milk yield (6.23Iitres) and it was the least for local cows (3.55 litres) when in milk. The study revealed the superiority of crossbred cows over the other breeds of milch animals in the study area. The study also indicated that the animals in the study area were kept with better breeding efficiency.